2019
DOI: 10.1007/s10803-019-04241-4
|View full text |Cite
|
Sign up to set email alerts
|

Adaptation to the Speed of Biological Motion in Autism

Abstract: Autistic individuals often present atypicalities in adaptation-the continuous recalibration of perceptual systems driven by recent sensory experiences. Here, we examined such atypicalities in human biological motion. We used a dual-task paradigm, including a running-speed discrimination task ('comparing the speed of two running silhouettes') and a change-detection task ('detecting fixation-point shrinkages') assessing attention. We tested 19 school-age autistic and 19 age-and ability-matched typical participan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
11
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(13 citation statements)
references
References 63 publications
0
11
2
Order By: Relevance
“…The results further show reduced perceptual adaptation, which can be interpreted as reduced use of the expectation of stimulus repetition to improve stimulus discrimination. However, one study indicated that this effect may be attention‐dependent [Karaminis et al, 2020], as we discuss below.…”
Section: Discussionmentioning
confidence: 88%
See 4 more Smart Citations
“…The results further show reduced perceptual adaptation, which can be interpreted as reduced use of the expectation of stimulus repetition to improve stimulus discrimination. However, one study indicated that this effect may be attention‐dependent [Karaminis et al, 2020], as we discuss below.…”
Section: Discussionmentioning
confidence: 88%
“…Four more studies [Karaminis, Arrighi, Forth, Burr, & Pellicano, 2020; Turi et al, 2015; Turi, Karaminis, Pellicano, & Burr, 2016; van Boxtel, Dapretto, & Lu, 2016] looked at perceptual adaptation to recent stimuli. In Section 3.2.2 (Perceptual Adaptation), we describe how this effect can be understood as an effect of predicting that subsequent stimuli will be similar.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations